Reclaiming Academia from Post-academia - Moriarty, Philip (Nature Publishing Group, 2008)
Post-academic science, driven as it is by commercialisation and market forces, is fundamentally at odds with core academic principles. Publicly-funded academics have an obligation to carry out science for the public good, a responsibility which is incompatible with the entrepreneurial ethos increasingly expected of university research by funding agencies.